Conductive material-zinc powder integrated material for zinc-rich / zinc-containing anticorrosive coating and preparation method thereof
Patent Information
- Application Number
- CN202611076106.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]针对传统环氧富锌涂层中锌粉利用率偏低、综合防护性能与力学性能不足、各组分间协同防腐机制尚不明确等关键问题,以提升锌粉利用效率、强化涂层多维度防护性能、系统阐释组分间协同防腐作用机理为核心研究目标,提出外延导电功能剂-锌粉一体化材料设计,精准构筑锌粉表面的外延导电域结构
[0043](1)通过创新的高温煅烧复合工艺,成功构筑了导电材料-锌粉一体化材料新型复合粉体。在该材料中,导电功能材料被牢固地接枝或固定于锌粉颗粒表面,形成外延性导电域,为锌粉颗粒安装了导电延伸臂。该结构从根本上解决了传统涂料中导电填料易团聚、与锌粉接触不良的技术难题。
Smart Images

Figure CN122978759A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an integrated conductive material-zinc powder material for zinc-rich / zinc-containing anti-corrosion coatings and its preparation method, belonging to the field of anti-corrosion coating technology. Background Technology
[0002] As the core structural material of modern industry, steel coating has become the mainstream technology for corrosion protection due to its low cost and strong adaptability. Epoxy zinc-rich coating has become the core technology in the field of heavy-duty corrosion protection, thanks to the corrosion protection mechanism of zinc powder electrochemical cathodic protection and epoxy resin physical shielding. It is widely used in key areas such as shipbuilding, marine engineering, and infrastructure construction.
[0003] Current research on zinc-rich epoxy coatings still faces several bottlenecks: First, the utilization rate of zinc powder is low. To ensure cathodic protection, a high zinc content (≥60% in non-volatile matter) needs to be maintained, but only 25%-33% of the zinc powder can effectively play its role. A large amount of zinc powder is isolated due to uneven dispersion or resin isolation, which not only wastes zinc resources and increases costs, but also leads to insufficient coating density, causing mechanical property deterioration, easy blistering and peeling. Second, there are defects in the application of conductive fillers. Nanofillers are prone to agglomeration and have poor compatibility with resin. Metal-based fillers are expensive and easy to oxidize, while metal oxide-based fillers have poor conductivity and the amount added is difficult to control. Third, the component synergy mechanism is unclear. The synergistic anti-corrosion mechanism between resin, zinc powder and conductive agent has not been fully clarified, making it difficult to achieve optimal performance matching. Fourth, conductive agents themselves agglomerate, or are located in large resin areas between zinc powders, becoming islands without conductive effect.
[0004] CNTS, as a typical representative of one-dimensional nanomaterials, possesses excellent electrical conductivity and outstanding chemical stability. Its unique structure and properties make it an ideal reinforcing phase for coating modification. Related studies have shown that when CNTS is uniformly dispersed in a coating, it can bridge zinc powder particles, forming a zinc powder-CNTS-zinc powder conductive chain, greatly improving the overall conductivity of the coating and enhancing the cathodic protection effect of zinc powder on the metal substrate. However, the core issues of CNTS agglomeration and precise construction of the conductive network remain unresolved. Although CNTS theoretically has great potential to improve the performance of epoxy zinc-rich coatings, it still faces many challenges in practical applications. For example, the dispersion problem of CNTS in coating systems urgently needs to be solved. Due to its high specific surface area and strong van der Waals forces, it is prone to agglomeration, severely affecting the realization of its performance advantages. Furthermore, improving the bridging conductivity between CNTS and zinc powder is also one of the keys to improving the protective performance of zinc-rich coatings.
[0005] In addition, carbon materials such as graphene and natural graphite possess excellent electrical conductivity, chemical stability, and mechanical strength, making them ideal modifiers for enhancing the protective performance of coatings. The sheet-like carbon-based materials, such as graphene and natural graphite, exhibit superior electrical conductivity, chemical stability, and mechanical strength. Their unique sheet-like morphology offers three core advantages: first, their high aspect ratio allows them to form a labyrinthine barrier structure within the coating, significantly extending the penetration path of corrosive media; second, their excellent electrical conductivity bridges dispersed zinc powder particles, constructing a continuous and stable conductive network and enhancing cathodic protection efficiency; and third, their high chemical inertness makes them less prone to reaction in corrosive environments, maintaining structural and performance stability over a long period, making them ideal coating modifiers. However, the sheet-like structure of graphene and graphite makes them prone to aggregation in epoxy groups, preventing the full realization of their performance advantages.
[0006] The aforementioned conductive agents all suffer from the problem of self-agglomeration or large resin areas within zinc powder particles becoming ineffective islands. Therefore, how to concentrate the conductive agent near the zinc powder particles, thereby precisely connecting the zinc powder, improving zinc powder utilization efficiency, and reducing the amount of conductive functional materials required, has become an important scientific issue for enhancing the protective performance of coatings. Summary of the Invention
[0007] Addressing key issues in traditional zinc-rich epoxy coatings, such as low zinc powder utilization, insufficient comprehensive protective and mechanical properties, and unclear synergistic anti-corrosion mechanisms among components, this research focuses on improving zinc powder utilization efficiency, enhancing the multi-dimensional protective performance of the coating, and systematically elucidating the synergistic anti-corrosion mechanism among components. It proposes an integrated material design combining epitaxial conductive functional agents and zinc powder, precisely constructing the epitaxial conductive domain structure on the zinc powder surface. Compared to pure zinc powder systems and blends of conductive additives, this integrated material significantly enhances the connectivity between zinc powder particles, forming a complete conductive network. This achieves the goal of strengthening the cathodic protection effect and long-term anti-corrosion performance of the coating while reducing the amount of conductive functional materials used.
[0008] A coating composition comprising component A and component B; component B is a curing agent component; component A comprises the following components by weight percentage: epoxy resin: 8-18 wt%; toughening resin: 0.5-2.5 wt%; solvent: 3-12 wt%; additives: 0.3-5.0 wt%; rust-preventive pigments and / or extender fillers: 10-30 wt%; conductive material-zinc powder integrated material: 40-75 wt%; wherein the conductive material-zinc powder integrated material comprises zinc powder particles and a conductive functional material fixed to the surface of the zinc powder particles by calcination.
[0009] The epoxy resin is selected from at least one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenolic epoxy resin, alicyclic epoxy resin or brominated epoxy resin.
[0010] The solvent is selected from at least one of xylene, toluene, ethylbenzene, n-butanol, isopropanol, ethylene glycol ether solvents, ketone solvents, or ester solvents;
[0011] The additive is selected from at least one of dispersants, thixotropic additives, defoamers, leveling agents, wax additives, fumed silica, adhesion promoters, or epoxy accelerators.
[0012] The rust-preventive pigment is selected from at least one of zinc phosphate, composite zinc phosphate, or environmentally friendly zinc phosphate.
[0013] The filler material is selected from at least one of barium sulfate, bentonite, or fumed silica.
[0014] The conductive functional material is selected from at least one of carbon nanotubes, graphene, graphite, conductive nickel, or copper-silver powder.
[0015] The content of the conductive functional material is 0.1-30 wt% based on the total mass of the integrated conductive material-zinc powder material.
[0016] The content of the conductive functional material is 0.3-20 wt%.
[0017] The content of the conductive functional material is 0.5-10 wt%.
[0018] The integrated conductive material-zinc powder material is prepared by dry mixing and calcination, liquid pre-dispersion and calcination, microwave calcination, or by bonding zinc powder particles and conductive functional materials together with a conductive polymer.
[0019] The conductive polymers mentioned refer to polyaniline, polypyrrole, polythiophene, polyacetylene, poly(p-styrene), poly(p-phenylene), or poly(3,4-ethylenedioxythiophene).
[0020] When the conductive functional material is carbon nanotube, its content is 0.3-5 wt%; or when the conductive functional material is graphene and / or graphite, its content is 0.5-10 wt%; or when the conductive functional material is conductive nickel, its content is 5-30 wt%.
[0021] Alternatively, when the conductive functional material is conductive nickel, zinc powder and nickel form an alloy.
[0022] When prepared by the dry mixing and calcination method, the steps include: (a) mixing and dispersing the powder, which is the conductive functional material, with zinc powder in an organic solvent to obtain a mixture; (b) performing solid-liquid separation and drying on the mixture of step (a) to obtain a physically mixed powder; (c) pressure binding the physically mixed powder of step (b) and pressing it into shape; (d) calcining the shape of step (c) under an oxygen-free or inert atmosphere; and (e) pulverizing and sieving the calcined product of step (d).
[0023] In the dry-mix calcination method, the pressing pressure in step (c) is 1-30 MPa; the calcination temperature in step (d) is 250-650℃, and the calcination time is 0.2-4h.
[0024] The preparation parameters of the dry-mix calcination method are further limited to: the pressing pressure in step (c) is 3-15 MPa;
[0025] The calcination temperature in step (d) is 320-480℃, and the calcination time is 0.5-2h.
[0026] When prepared by the liquid pre-dispersion calcination method, the steps include: (a) mixing and dispersing a pre-dispersion liquid containing the conductive functional material with zinc powder to obtain a mixture; (b) performing solid-liquid separation and drying on the mixture of step (a) to obtain a physically mixed powder; (c) pressure binding the physically mixed powder of step (b) and pressing it into shape; (d) calcining the shaped product of step (c) under an oxygen-free or inert atmosphere; and (e) pulverizing and sieving the calcined product of step (d).
[0027] In the liquid pre-dispersion calcination method, the solid content of the conductive functional material in the pre-dispersion liquid in step (a) is 1-10 wt%; the pressing pressure in step (c) is 2-30 MPa; and the calcination temperature in step (d) is 250-650℃ and the calcination time is 0.2-4 h.
[0028] During the preparation of the integrated conductive material-zinc powder material, the resistivity of the resulting integrated conductive material-zinc powder material is kept within a set range by controlling the amount of conductive functional material added and the pressing pressure; the resistivity is calculated using the following formula: ;
[0029] In the formula, It is the resistivity of the composite material. It is the load of the conductive material. It is the applied pressure value. , , These are the parameters to be fitted.
[0030] A method for preparing the coating composition includes the following steps:
[0031] (1) Mix and disperse epoxy resin, toughening resin, dispersant and solvent, then add anti-rust pigment and / or extender filler and other additives and grind and disperse to obtain coating base material;
[0032] (2) Under stirring conditions, the conductive material-zinc powder integrated material is added to the coating base prepared in step (1) and mixed evenly to obtain component A;
[0033] (3) Mix the curing agent with the solvent and / or additives evenly to obtain component B.
[0034] In step (1), the fineness of the coating base material after grinding and dispersion is ≤80μm.
[0035] In step (1), the fineness of the coating base material after grinding and dispersion is ≤50μm.
[0036] In step (2), the stirring speed is 300-2000 rpm and the stirring time is 5-90 min.
[0037] A method for preparing a coating is obtained by the coating composition, comprising the following steps: (b) mixing component A and component B to obtain a mixed coating; (c) applying the mixed coating to the surface of a metal substrate; and (d) curing the coated metal substrate to form a coating.
[0038] Prior to step (b), the application viscosity of the mixed coating is adjusted to 20-80 s (Ford Cup 4) using a solvent; the curing temperature in step (c) is 15-60°C, and the dry film thickness of the coating is 10-150 μm.
[0039] The shielding resistance of the coating is measured by controlling the amount of conductive functional material added and the soaking time. The shielding resistance is calculated using the following formula for the impedance modulus at a low frequency of 0.01 Hz. get:
[0040]
[0041] The soaking time is And the carbon nanotube loading is When the coating is in impedance magnitude at Hz Soaking time, It is the carbon nanotube loading capacity, It is the initial low-frequency impedance scale, It is the reference diffusion characteristic time constant, It is the characteristic loading of carbon nanotube network effect.
[0042] The beneficial effects of this invention are:
[0043] (1) A novel composite powder integrating conductive material and zinc powder was successfully constructed through an innovative high-temperature calcination composite process. In this material, the conductive functional material is firmly grafted or fixed to the surface of the zinc powder particles to form an extended conductive domain, thus providing conductive extension arms for the zinc powder particles. This structure fundamentally solves the technical problems of easy agglomeration of conductive fillers and poor contact with zinc powder in traditional coatings.
[0044] (2) The integrated structure creates a highly efficient and stable three-dimensional conductive network between zinc powder particles, which greatly improves the conductivity of the entire zinc powder system. This allows more zinc powder in the coating to participate in the electrochemical protection process, thereby achieving a superior cathodic protection effect compared to traditional high-content pure zinc-rich coatings with the same or even lower zinc powder content, and significantly improving the utilization efficiency of zinc resources.
[0045] (3) The coating prepared using the integrated material of the present invention exhibits significantly better impedance, shielding resistance and corrosion resistance than traditional pure zinc-rich coatings and simple physical blending systems under long-term harsh corrosive environments (and electrochemical tests). The integrated strategy slows down the rate of degradation of coating performance and achieves a leapfrog long-term protection.
[0046] (4) The coating of the present invention not only greatly improves the anti-corrosion performance, but also effectively enhances its adhesion. Furthermore, the original key mechanical properties of the coating, such as flexibility and impact resistance, are not negatively affected. It fully meets the actual application requirements of heavy anti-corrosion fields such as bridges, ships, and marine engineering, and demonstrates great potential for industrial application.
[0047] (5) The physical prediction model precisely constructed in this invention systematically elucidates the coupling law of carbon nanotube loading and applied pressure on coating resistivity. It not only provides theoretical support for the performance optimization of conductive material-zinc powder integrated material, but also reveals the multiplication effect of the epitaxial conductive domain formed by carbon nanotubes on the zinc powder surface on the conductive path by fitting constants and quantitative analysis. This guides the precise control of pressure and the optimal ratio of carbon nanotube loading in the production process, greatly improving the utilization efficiency of zinc powder and strengthening the cathodic protection effect of the coating.
[0048] (6) This invention establishes a low-frequency impedance prediction method based on diffusion control and network enhancement mechanism. It unifies the electrolyte penetration effect caused by immersion time and the enhanced tortuosity of the percolation network and diffusion path caused by carbon nanotube loading into the same physical model. With a small number of parameters, the attenuation law of the coating shielding ability with service time can be quantitatively characterized, and the system differences of impedance attenuation rate and failure characteristic time under different conditions can be represented. Thus, it can realize the interpretable prediction of the long-term protective performance of the coating and the guidance for formula optimization, and provide a clear quantitative basis for the construction of conductive network and the design of corrosion protection life. Attached Figure Description
[0049] Figure 1 SEM images of zinc powder-A, CNTS-B, and CNTS / Zn integrated material-C;
[0050] Figure 2 The resistivity of physically mixed CNTS / Zn materials and CNTS / Zn integrated materials with different contents;
[0051] Figure 3 : Curve showing the change in shielding resistance of the coating over immersion time;
[0052] Figure 4 Salt spray test results of CNTS / Zn integrated material coating: Pure zinc E20 epoxy coating: H-60-E20 (360h), H-70-E20 (360h); a-0.5%CNTS / ZnPB (720h); b-1%CNTS / ZnPB (720h); c-1.5%CNTS / ZnPB (720h); A-0.5%CNTS / Zn (720h); B-1%CNTS / Zn (720h); C-1.5%CNTS / Zn (720h);
[0053] Figure 5 Salt spray test results of the coatings of graphene-zinc powder physical blend and calcined integrated materials: Pure zinc E20 epoxy coating: H-60-E20 (360h), H-70-E20 (360h); a (1%Gr / ZnPB-720h); b (5%Gr / ZnPB-720h); c (1%Gr / Zn-720h); d (5%Gr / Zn-720h); Pure zinc E44 epoxy coating: H-600-E44 (2000h), H-700-E44 (2000h); A (1%Gr / ZnPB-2000h); B (5%Gr / ZnPB-2000h); C (1%Gr / Zn-2000h); D (5%Gr / Zn-2000h).
[0054] Figure 6 : Comparison of calculated values with true values in the fitted samples of resistivity prediction calculation;
[0055] Figure 7 : Comparison of calculated values with actual values in the validation sample for resistivity prediction calculation;
[0056] Figure 8 : Comparison of calculated values and actual values in the full sample of resistivity prediction calculations;
[0057] Figure 9 : Comparison between the calculated values and the true values in the fitting sample of impedance modulus prediction calculation;
[0058] Figure 10 : Comparison of calculated values with actual values in the verification sample for impedance modulus prediction;
[0059] Figure 11 : Comparison of calculated values and true values in the full sample for impedance modulus prediction;
[0060] Figure 12 : A schematic diagram of the technical solution of this patent. Detailed Implementation
[0061] The following provides a detailed description of several embodiments of the present invention. It should be understood that these embodiments are merely illustrative of the technical solutions of the present invention and are not intended to limit the invention to the specific forms explicitly described. Without departing from the technical concept of the present invention, those skilled in the art can appropriately select or combine the types of materials, proportions, processing methods, and process conditions. Unless otherwise stated, all percentage contents mentioned in this specification are mass percentage contents; the numerical ranges include their endpoints and any values and sub-ranges located between the endpoints. When a component is described as being selected from at least one of several materials, the component can be any one of the materials or a combination of two or more of the materials.
[0062] I. Conductive Materials - Integrated Zinc Powder Materials
[0063] In some embodiments, the present invention provides a conductive material-zinc powder integrated material for zinc-rich or zinc-containing anti-corrosion coatings. The integrated material comprises zinc powder particles and a conductive functional material composited with the zinc powder particles, wherein the conductive functional material is at least partially located on the surface of the zinc powder particles and forms an integrated composite structure with the zinc powder particles.
[0064] The term "conductive material-zinc powder integrated material" as used in this article refers to a conductive functional material that does not exist merely as a loose powder independent of zinc powder, but is fixed to the surface of zinc powder particles through calcination, microwave treatment, conductive polymer bonding, or a combination thereof, or forms a stable bond on the surface of zinc powder particles and between adjacent zinc powder particles. This fixing can include adhesion, coating, winding, embedding, grafting, welding, sintering, alloying, or a combination of the above methods.
[0065] In some embodiments, calcination in an oxygen-free or inert atmosphere softens or slightly melts the surface of the zinc powder particles, thereby fixing the conductive functional material to the surface of the zinc powder particles. The conductive functional material can extend outward from the surface of the zinc powder particles to form an epitaxial conductive domain or conductive extension structure. The epitaxial conductive domain can increase the effective conductive range of the zinc powder particles and form conductive bridges between adjacent zinc powder particles.
[0066] In some embodiments, a conductive functional material particle or structure may simultaneously contact two or more zinc powder particles, thereby forming a conductive pathway of "zinc powder—conductive functional material—zinc powder". Multiple such conductive pathways may be interconnected to form a three-dimensional conductive network within the integrated material and the coating formed therefrom.
[0067] The zinc powder can be zinc powder suitable for zinc-rich or zinc-containing anti-corrosion coatings. The zinc powder particles can be spherical, near-spherical, flake-like, irregularly shaped, or a combination thereof. In one specific embodiment, the zinc powder is 600 mesh zinc powder.
[0068] In some embodiments, the conductive functional material is selected from at least one of carbon nanotubes, graphene, graphite, conductive nickel, copper-silver powder, and other conductive materials.
[0069] The carbon nanotubes can be single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof. Carbon nanotubes can be used in powder form or in pre-dispersed liquid form. The carbon nanotubes have a one-dimensional extended structure; after being fixed to the surface of zinc powder particles, they can form conductive arms extending outward from the zinc powder surface and can wrap around or bridge adjacent zinc powder particles.
[0070] The graphene may include single-layer graphene, few-layer graphene, multilayer graphene, or combinations thereof. The sheet-like structure of graphene can overlap between adjacent zinc powder particles to form conductive pathways. In coatings formed from the integrated material, graphene can also form sheet-like barrier structures that extend the penetration path of corrosive media.
[0071] The graphite can be natural graphite, flake graphite, or other conductive graphite materials. Graphite can be in the form of flakes, irregular granules, or a combination thereof. Graphite is fixed to the surface of the zinc powder particles and / or distributed between adjacent zinc powder particles, thereby promoting electron transfer between the zinc powder particles.
[0072] The conductive nickel can be nickel powder or other nickel-containing conductive materials capable of forming a conductive composite structure with zinc powder. In some embodiments, the conductive nickel and zinc powder form an alloying interface during calcination. In other embodiments, zinc and nickel at least partially form a zinc-nickel alloy.
[0073] The copper-silver powder can be a copper-based conductive powder with silver on its surface, such as silver-plated copper powder. The copper-silver powder can be fixed to the surface of zinc powder particles by calcination to establish a metallic conductive path between the zinc powder particles.
[0074] In some embodiments, the content of the conductive functional material is 0.1 to 30 wt% based on the total mass of the conductive material-zinc powder integrated material. In other embodiments, the content is 0.3 to 20 wt%; in further embodiments, the content is 0.5 to 10 wt%.
[0075] The content of different types of conductive functional materials can be selected based on their morphology, conductivity, and loading state on the zinc powder surface. For example, when the conductive functional material contains carbon nanotubes, the content of carbon nanotubes can be 0.3–2.0 wt% based on the total mass of the integrated material. When the conductive functional material contains graphene and / or graphite, the total content of graphene and graphite can be 0.5–10 wt% based on the total mass of the integrated material. When the conductive functional material contains conductive nickel, the content of conductive nickel can be 5–30 wt% based on the total mass of the integrated material.
[0076] In other embodiments, the integrated material comprises two or more conductive functional materials. For example, it may simultaneously comprise carbon nanotubes and graphene, carbon nanotubes and graphite, graphene and graphite, carbon nanotubes and conductive nickel, or carbon materials and copper-silver powder. Conductive functional materials with different morphologies can be jointly fixed on the surface of zinc powder particles and form an overlapping conductive structure.
[0077] II. Preparation of Conductive Material-Zinc Powder Integrated Material
[0078] The integrated material of the present invention can be prepared by powder premixing and calcination, liquid predispersing and calcination, microwave calcination, conductive polymer bonding, or a combination thereof.
[0079] 1. Powder premixing and calcination method
[0080] In some embodiments, the conductive material-zinc powder integrated material is prepared by a powder premixing and calcination method. The method includes the following steps:
[0081] (a) The powdered conductive functional material is mixed and dispersed with zinc powder in an organic solvent to obtain a mixture containing zinc powder and conductive functional material;
[0082] (b) The mixture is subjected to solid-liquid separation and drying to obtain a physically mixed powder of conductive functional material and zinc powder;
[0083] (c) Apply pressure to the physically mixed powder to make the conductive functional material and zinc powder particles come into close contact with each other, and press the physically mixed powder into shape;
[0084] (d) Calcination of the pressed material under vacuum, oxygen-free atmosphere, or inert atmosphere to fix the conductive functional material onto the surface of the zinc powder particles; and
[0085] (e) The calcined product is cooled, crushed and sieved to obtain an integrated conductive material-zinc powder material.
[0086] In step (a), an organic solvent is used to assist in the mixing and dispersion of zinc powder and the conductive functional material. The organic solvent may include xylene, or other organic solvents capable of dispersing the corresponding conductive functional material and which can be removed in subsequent steps.
[0087] Mixing and dispersion can be achieved through stirring, shearing dispersion, grinding dispersion, or a combination thereof. In some embodiments, the conductive functional material is first gradually added to the material containing zinc powder and organic solvent under stirring, and then dispersed at low speed using grinding media to promote the uniform distribution of the conductive functional material around the zinc powder particles. The grinding media may be zirconium beads.
[0088] The solid-liquid separation in step (b) can be performed by filtration, vacuum filtration, centrifugation, or a combination thereof. Drying can be carried out under normal or reduced pressure, preferably by vacuum drying. The organic solvent is removed by drying to obtain a physically mixed powder that can be pressed.
[0089] The pressure bonding in step (c) creates close contact between the conductive functional material and the zinc powder particles, as well as between different zinc powder particles, which facilitates the formation of stable interfacial bonds during subsequent calcination. The physically mixed powder can be pressed into cakes, blocks, sheets, or other shaped bodies suitable for calcination.
[0090] In some embodiments, the pressing pressure is 1–30 MPa. In other embodiments, the pressing pressure is 3–15 MPa. The pressing pressure can be adjusted according to the zinc powder particle size, the type of conductive functional material, the size of the molded body, and the required degree of particle contact.
[0091] The calcination in step (d) is carried out under conditions of limited oxygen contact to reduce oxidation of the zinc powder and conductive functional materials during heating. The inert atmosphere may be provided by nitrogen, argon, or other protective gases that do not react adversely with the materials to be treated.
[0092] The calcination temperature can be 250–650°C, and the calcination time can be 0.2–4 hours. In some embodiments, the calcination temperature is 320–480°C, and the calcination time is 0.5–2 hours. In a further embodiment, the molded article can be gradually heated to the required calcination temperature and held at that temperature. The heating can be done using a gradient heating method to reduce rapid temperature changes in the molded article.
[0093] In some embodiments, the calcination temperature is selected to soften or slightly melt the surface of the zinc powder particles without causing uncontrolled melting and aggregation of the zinc powder as a whole. The softening or slight melting of the zinc powder particle surface allows the conductive functional material to be at least partially embedded or adhered to the zinc powder surface. In other embodiments, calcination can also cause the metallic conductive functional material to form a sintered bond or alloying interface with zinc.
[0094] In step (e), the calcined molded body is cooled and then pulverized to reform a powder suitable for coating formulation. The pulverized product may be sieved once or multiple times to remove excessively large agglomerated particles and control the particle size of the monolithic material. In some embodiments, the pulverized product is sieved sequentially through a coarser screen and a finer screen. In a further embodiment, a 200-mesh screen and a 400-mesh screen may be used for sieving.
[0095] 2. Liquid pre-dispersion calcination method
[0096] In other embodiments, a liquid pre-dispersion calcination method is used to prepare an integrated conductive material-zinc powder material. This method is particularly suitable for carbon nanotubes, graphene, or other nanomaterials that are prone to agglomeration.
[0097] The method may include the following steps:
[0098] (a) A pre-dispersed liquid containing conductive functional materials is mixed and dispersed with zinc powder to obtain a mixture;
[0099] (b) The mixture is subjected to solid-liquid separation and drying to obtain a physically mixed powder;
[0100] (c) Apply pressure to the physically mixed powder and press it into shape;
[0101] (d) Calcination of the pressed material under vacuum, oxygen-free atmosphere, or inert atmosphere; and
[0102] (e) The calcined product is cooled, crushed and sieved to obtain an integrated conductive material-zinc powder material.
[0103] The pre-dispersion liquid comprises a conductive functional material and a liquid dispersion medium, and may also contain dispersion components for maintaining the dispersion state of the conductive functional material. The solid content of the conductive functional material may be 1–10 wt% based on the total mass of the pre-dispersion liquid.
[0104] In one embodiment, the pre-dispersion liquid is a carbon nanotube pre-dispersion liquid. Before mixing the carbon nanotube pre-dispersion liquid with zinc powder, the carbon nanotubes have at least partially depolymerized and dispersed in the liquid medium, thus reducing the degree of agglomeration when the carbon nanotubes are added directly in dry powder form.
[0105] In step (c), the pressing pressure can be 2–30 MPa. In step (d), the calcination temperature can be 250–650 °C, and the calcination time can be 0.2–4 hours. The atmosphere control, heating method, pulverization, and sieving methods in the liquid pre-dispersion calcination method can adopt the corresponding methods described in the aforementioned powder premixing calcination method.
[0106] By pre-dispersing the conductive material in liquid before pressure binding and calcination, the conductive functional material can be more evenly distributed and fixed on the surface of zinc powder particles, reducing the possibility of the conductive functional material forming independent agglomerates.
[0107] 3. Microwave calcination method
[0108] In other embodiments, microwave calcination can be used to integrate the conductive functional material with zinc powder into a single structure.
[0109] In this method, the conductive functional material is first mixed with zinc powder, which can be done by powder premixing or liquid predispersing. The mixture is then dried and optionally pressure-bonded. Subsequently, the mixture is microwave-heated under a vacuum, oxygen-free atmosphere, or inert atmosphere to form a fixed bond between the zinc powder particles and the conductive functional material. The microwave-treated material is then cooled, pulverized, and sieved to obtain an integrated conductive material-zinc powder material.
[0110] Microwave heating conditions can be selected based on the particle size of the zinc powder, the microwave absorption performance of the conductive functional material, the material quantity, and the required degree of interfacial bonding. Microwave treatment is preferably performed to fix the conductive functional material onto the surface of the zinc powder particles, while avoiding undesirable over-melting or agglomeration of the zinc powder particles.
[0111] 4. Conductive polymer bonding method
[0112] In some other embodiments, a conductive polymer can be used to bond zinc powder particles to a conductive functional material to form an integrated conductive material-zinc powder material.
[0113] The conductive polymer may be selected from polyaniline, polypyrrole, polythiophene, polyacetylene, poly(p-styrene), poly(p-phenylene), poly(3,4-ethylenedioxythiophene), and combinations thereof.
[0114] In some embodiments, zinc powder, conductive functional material, and conductive polymer or its precursor are first mixed, such that the conductive polymer is distributed between the zinc powder particles and the conductive functional material. The conductive polymer can be pre-formed before mixing or formed in the presence of zinc powder and conductive functional material. The conductive polymer forms a conductive adhesive layer or connecting structure on the surface of the zinc powder particles, thereby fixing the conductive functional material to the surface of the zinc powder particles and establishing conductive connections between different zinc powder particles.
[0115] In other embodiments, the conductive polymer bonding method can be used in conjunction with calcination or microwave treatment. For example, conductive functional materials can be pre-fixed to the surface of zinc powder particles using a conductive polymer before subsequent heat treatment; or a calcined integral material can be formed first, and then a conductive polymer can be applied to its surface to further connect adjacent composite particles.
[0116] III. Zinc-rich or zinc-containing coatings that incorporate integrated materials
[0117] The present invention also provides a zinc-rich or zinc-containing anti-corrosion coating comprising the above-mentioned conductive material-zinc powder integrated material. The coating may be a solvent-based coating, a water-based coating, or a powder coating.
[0118] In some embodiments, the conductive material-zinc powder integrated material has a mass fraction of 30–85 wt% in the coating or the coating formed by the coating. In other embodiments, its mass fraction is 40–75 wt%. The specific content of the integrated material can be selected according to the resin system, coating thickness, application method, and the required level of cathodic protection.
[0119] Conductive material-zinc powder integrated materials can replace some or all of the ordinary zinc powder in traditional zinc-rich coatings. Because the conductive functional material is pre-fixed on the surface of the zinc powder particles, it is not easy to completely separate from the zinc powder during coating formulation and coating formation, thus helping to keep the conductive functional material near the zinc powder particles.
[0120] 1. Two-component epoxy coating
[0121] In some embodiments, the coating is a two-component epoxy zinc-rich or zinc-containing coating, comprising component A and component B. Component A is the main component containing epoxy resin and an integrated conductive material-zinc powder material, and component B is the curing agent component.
[0122] Based on the total mass of component A, component A may include the following components:
[0123] Epoxy resin: 8-18 wt%
[0124] Toughening resin: 0.5–2.5 wt%;
[0125] Solvent: 3-12 wt%
[0126] Additives: 0.3–5.0 wt%;
[0127] Rust-preventive pigments and / or extender fillers: 10–30 wt%;
[0128] Conductive material-zinc powder integrated material: 30-85wt%.
[0129] The content of each component can be selected within the above range, and the total amount of each component in component A is 100wt%.
[0130] The epoxy resin can be selected from bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenolic epoxy resin, alicyclic epoxy resin, brominated epoxy resin, and combinations thereof. In some embodiments, the epoxy resin is a bisphenol A type epoxy resin. Epoxy resins with corresponding epoxy values can be selected according to the required crosslinking density, workability, flexibility, and corrosion resistance.
[0131] The toughening resin is used to improve the toughness, impact resistance, or adhesion to metal substrates of the cured coating. The toughening resin can be used alone or pre-mixed with epoxy resin.
[0132] The solvent may be selected from xylene, toluene, ethylbenzene, n-butanol, isopropanol, ethylene glycol ether solvents, ketone solvents, ester solvents, and combinations thereof. In some embodiments, the solvent comprises a combination of aromatic solvents and alcohol solvents, such as a combination of xylene and n-butanol. The type and amount of solvent can be selected based on the solubility of the epoxy resin and toughening resin, the storage stability of the coating, and the application viscosity.
[0133] The additives may be selected from dispersants, thixotropic additives, defoamers, leveling agents, wax additives, fumed silica, adhesion promoters, epoxy accelerators, and combinations thereof.
[0134] Dispersants can be used to promote the dispersion of rust-preventive pigments, extender fillers, and other solid components in a resin medium. Thixotropic additives can be used to adjust the rheological properties of coatings and reduce sedimentation during storage. The wax additives may include polyamide waxes. Fumed silica can have thixotropic, anti-settling, or filler effects. Adhesion promoters can be used to improve the interfacial bonding between the coating and the metal substrate. Epoxy accelerators can be used to regulate the curing reaction between the epoxy resin and the curing agent.
[0135] The rust-preventive pigment can be selected from zinc phosphate, composite zinc phosphate, environmentally friendly zinc phosphate, and combinations thereof. The rust-preventive pigment can be used in conjunction with conductive materials—integrated zinc powder materials—to provide auxiliary rust prevention.
[0136] The extender filler can be selected from barium sulfate, bentonite, fumed silica, and combinations thereof. The extender filler can be used to adjust the mechanical properties, rheological properties, volumetric solids content, and shielding performance of the coating.
[0137] Component B contains an epoxy curing agent capable of curing with the epoxy resin in component A. The epoxy curing agent may be mixed with a solvent and / or additives to form a curing agent component. The solvent in component B may be a solvent compatible with component A, such as xylene, n-butanol, or combinations thereof. Component B may also contain additives for improving curing, application, or coating properties.
[0138] Component A and component B are stored separately and mixed before coating in a proportion that allows the epoxy groups to fully react with the active groups of the curing agent.
[0139] 2. Water-based coatings and powder coatings
[0140] In other embodiments, the conductive material-zinc powder integrated material can be incorporated into the waterborne anti-corrosion coating. The waterborne anti-corrosion coating comprises a waterborne film-forming resin, a waterborne curing component or crosslinking component, and the integrated material. The integrated material is dispersed in the waterborne film-forming system and, after film formation, forms an anti-corrosion coating comprising zinc powder and epitaxial conductive domains.
[0141] In other embodiments, the conductive material-zinc powder integrated material can be used in powder coatings. The powder coating comprises a powder film-forming resin, optional curing components, additives, and the integrated material. The components are dry-mixed, melt-mixed, pulverized, and sieved to form an applyable powder coating, or the integrated material is mixed with a pre-prepared powder coating base. After application and heat curing, the powder coating forms a corrosion-resistant coating containing the integrated material on the surface of a metal substrate.
[0142] IV. Preparation of Coating Compositions
[0143] In some embodiments, two-component epoxy coatings can be prepared according to the following methods.
[0144] First, epoxy resin, toughening resin, dispersant, and at least a portion of solvent are added to a mixing device for mixing and dispersion. Then, rust-inhibiting pigments and / or extender fillers, along with other necessary additives, are added, and the mixture is ground and dispersed to obtain the coating base.
[0145] The grinding and dispersion can be achieved using zirconium beads or other abrasive media suitable for coatings. The fineness of the ground coating base can be no greater than 80 μm. In some embodiments, the fineness is no greater than 50 μm.
[0146] The integrated material is preferably added to the coating base after the anti-rust pigments and extender fillers have been ground, thereby reducing the damage to the conductive extension structures fixed on the zinc powder surface during the grinding process. Under stirring conditions, the conductive material-zinc powder integrated material is gradually added to the coating base and mixed until it is evenly distributed to obtain component A.
[0147] The stirring speed when adding the integrated material can be 300–2000 rpm, and the stirring time can be 5–90 minutes. The stirring conditions can be adjusted according to the batch size, equipment structure, coating viscosity, and the amount of integrated material added. Ideally, the stirring should ensure uniform distribution of the integrated material without excessively damaging its composite structure.
[0148] Component B can be prepared by mixing an epoxy curing agent with a solvent and / or additives. During mixing, the curing agent, solvent, and additives should be evenly distributed. Components A and B should be packaged and stored separately and mixed before use.
[0149] V. Preparation of Anti-corrosion Coating
[0150] The present invention also provides a method for forming an anti-corrosion coating on a metal substrate using the above-mentioned zinc-rich or zinc-containing coating. The method may include:
[0151] (a) Mix component A and component B to obtain a mixed coating;
[0152] (b) Applying the mixed coating to the surface of a metal substrate; and
[0153] (c) Curing the mixed coating applied to the surface of the metal substrate to form an anti-corrosion coating.
[0154] The metal substrate can be a steel substrate or other metal substrates that require cathodic protection and shielding. Before coating, the metal substrate can be degreased, derusted, sandblasted, polished, or subjected to other surface treatments as needed.
[0155] Before coating, the application viscosity of the mixed coating can be adjusted using a solvent. In some embodiments, the application viscosity, measured with a Coat 4 cup, is 20–80 seconds. The application viscosity can be adjusted depending on whether spraying, brushing, rolling, or other coating methods are used.
[0156] The mixed coating can be applied to the surface of a metal substrate by spraying, brushing, rolling, or other methods suitable for anti-corrosion coatings. In some embodiments, a wet film is formed by spraying.
[0157] The applied coating can cure at 15–60°C. Curing can be carried out at ambient temperature or accelerated by appropriate heating. The resulting dry film thickness can range from 10–150 μm. The specific dry film thickness can be selected based on the metal substrate's operating environment, corrosion resistance requirements, resin system, and number of applications.
[0158] In the cured coating, the conductive functional material fixed to the surface of the zinc powder particles can form conductive bridges between adjacent zinc powder particles, enabling more zinc powder particles to establish electrical connections with the metal substrate. One-dimensional conductive materials such as carbon nanotubes can form conductive extension arms; sheet-like materials such as graphene and graphite can simultaneously form conductive overlapping structures and sheet-like barrier structures; and metallic conductive materials can form metallic conductive connections. Thus, the cathodic protection effect of zinc powder, together with the physical shielding effect of the resin matrix and sheet-like materials, can constitute the anti-corrosion system of the coating.
[0159] The following raw materials were used in the following embodiments:
[0160] Reagent Material Name Specification Manufacturer Epoxy resin E44 Sichuan Sanmu Chemical Co., Ltd. Epoxy resin E20 Jiangxi Qingzhu Technology Co., Ltd. Toughened resin LA300 Jiadida New Materials Co., Ltd. dispersant JS-225 Dongguan Jingshang New Materials Development Co., Ltd. Polyamide wax Z15 Chengdu Haizhichen Trading Co., Ltd. Adhesion promoter 1051 Quanzhou Haimingsiyi Trading Co., Ltd. Epoxy curing agent 498 Shenzhen Jiadida New Material Technology Co., Ltd. Additives 1121 Taiwan Deqian Zinc powder 600 mesh Sichuan Xinweiling Metal New Materials Co., Ltd. carbon nanotube powder CNTS Suzhou Gaotong New Materials Co., Ltd. carbon nanotube dispersion 4wt% graphene (D-CNTS) Suzhou Gaotong New Materials Co., Ltd.
[0161] Example 1: Preparation of an integrated conductive functional material-zinc powder material
[0162] This embodiment employs a powder premixing-pressure bonding-oxygen-free calcination method to prepare an integrated conductive functional material—zinc powder. The conductive functional materials used are carbon nanotubes, graphene, graphite, nickel powder, and copper-silver powder.
[0163] Weigh 100g of zinc powder with a particle size of 600 mesh and place it in a dispersion container. Add 20g of xylene. While stirring in a disperser at 300 rpm, slowly add the predetermined amount of conductive functional material to the zinc powder. After the addition is complete, add zirconium beads to the dispersion container and continue dispersing at 600 rpm for 30 minutes to ensure that the conductive functional material and zinc powder are fully mixed.
[0164] After dispersion, the mixture is filtered using a vacuum filter to remove the liquid phase. The resulting solid is then dried in a vacuum drying apparatus to obtain a physical mixture of conductive functional material and zinc powder, denoted as "Conductive Functional Material / Zn PB".
[0165] The above-mentioned physically mixed powder was placed in a mold and pressed into a cake shape using a press with a force of 10T. The resulting cake was placed in an oxygen-free calcination chamber and heated from room temperature to 400℃ at a heating rate of 5℃ / min, and held at 400℃ for 1 hour. After calcination, it was cooled to room temperature under oxygen-free conditions, and the calcined product was removed and pulverized. The pulverized material was first sieved through a 200-mesh sieve, and then sieved through a 400-mesh sieve with an aperture of approximately 38μm to obtain a conductive functional material—a zinc powder integrated material—with conductive functional material fixed on the surface of zinc powder particles.
[0166] Table 1 shows the different conductive functional materials and their addition amounts. The addition ratios and sample names in Table 1 are based on 100 parts by weight of zinc powder. For example, "0.5% CNTS / Zn" means that 0.5 parts by weight of carbon nanotubes are added relative to 100 parts by weight of zinc powder.
[0167] Table 1 Raw material composition of zinc powder integrated materials with different conductive functions
[0168] 0.5% CNTS / Zn 100 carbon nanotubes 0.5 1%CNTS / Zn 100 carbon nanotubes 1.0 1.5% CNTS / Zn 100 carbon nanotubes 1.5 1%Gr / Zn 100 graphene 1.0 2.5%Gr / Zn 100 graphene 2.5 5%Gr / Zn 100 graphene 5.0 1%G / Zn 100 graphite 1.0 2.5% G / Zn 100 graphite 2.5 5% G / Zn 100 graphite 5.0 10% Ni / Zn 100 Nickel powder 10.0 15% Ni / Zn 100 Nickel powder 15.0 20% Ni / Zn 100 Nickel powder 20.0 1%Cu-Ag / Zn 100 Copper silver powder 1.0 2.5% Cu-Ag / Zn 100 Copper silver powder 2.5 5% Cu-Ag / Zn 100 Copper silver powder 5.0
[0169] During the aforementioned pressure bonding and anaerobic calcination process, the conductive functional material maintains close contact with the zinc powder particles. Because 400℃ is close to the melting point of zinc, the surface of the zinc powder particles softens or slightly melts, fixing carbon nanotubes, graphene, graphite, nickel powder, or copper-silver powder onto the surface of the zinc powder particles. After cooling, pulverizing, and sieving, a conductive functional material-zinc powder integrated composite powder is obtained, capable of forming epitaxial conductive domains on the surface of the zinc powder particles.
[0170] Example 2: Preparation of integrated carbon nanotube-zinc powder material by liquid pre-dispersion calcination method
[0171] This embodiment uses a liquid pre-dispersion calcination method to prepare an integrated carbon nanotube-zinc powder material. The carbon nanotube pre-dispersion liquid used is denoted as D-CNTS, in which the solid content of carbon nanotubes is 4wt%.
[0172] Weigh the carbon nanotube predispersant and zinc powder according to the proportions shown in Table 3. While stirring the carbon nanotube predispersant in a disperser at 300 rpm, slowly add the zinc powder to the carbon nanotube predispersant to obtain a mixture. Then add zirconium beads to the mixture and disperse at 600 rpm for 30 minutes to ensure thorough mixing of the carbon nanotubes and zinc powder.
[0173] After dispersion, the mixture was separated into solid and liquid phases using a vacuum filter, and the resulting solid was dried under vacuum to obtain a physical mixture of carbon nanotubes and zinc powder, denoted as D-CNTS / Zn PB.
[0174] The obtained D-CNTS / Zn PB was pressed into a disc shape using a press with a force of 10T. The disc was then placed in an oxygen-free calcination chamber and heated to 400℃ at a rate of 5℃ / min, and calcined at 400℃ for 1 hour. After calcination, the material was cooled under oxygen-free conditions, removed, and ground. The resulting product was then sieved through a 200-mesh sieve and a 400-mesh sieve to obtain a carbon nanotube-zinc powder integrated material with carbon nanotubes fixed on the surface of zinc powder particles, denoted as D-CNTS / Zn.
[0175] The specific amounts of carbon nanotube predispersant and zinc powder are shown in Table 3.
[0176] Table 3. Ratio of carbon nanotube predispersant to zinc powder
[0177] 1%D-CNTS / Zn 100 25.0 1.0 1.5% D-CNTS / Zn 100 37.5 1.5
[0178] In the sample names, "1%" and "1.5%" represent the percentage of carbon nanotube solid mass relative to zinc powder mass, respectively. Based on the total mass of carbon nanotubes and zinc powder, the theoretical mass fraction of carbon nanotubes in the 1%D-CNTS / Zn and 1.5%D-CNTS / Zn integrated materials is approximately 0.99wt% and 1.48wt%, respectively.
[0179] By pre-dispersing carbon nanotubes, entanglement and aggregation between them can be reduced, resulting in a more uniform distribution of carbon nanotubes on the surface of zinc powder particles. After pressure bonding and anaerobic calcination, the carbon nanotubes are fixed to the surface of the zinc powder particles and can form conductive extension structures between adjacent zinc powder particles.
[0180] Example 3: Preparation of an integrated conductive material-zinc powder epoxy zinc-rich coating and coating layer
[0181] In this embodiment, two-component epoxy zinc-rich coatings were prepared using E20 epoxy resin and E44 epoxy resin, respectively. Component A is the main component containing an integrated conductive material and zinc powder, and component B is the curing agent component. Unless otherwise specified, "parts" in this embodiment refers to parts by weight.
[0182] (1) Preparation of component A
[0183] Component A is made from the following raw materials in parts by weight:
[0184] Epoxy resin: 12 parts;
[0185] LA300 toughening resin: 1 part;
[0186] JS-225 dispersant: 0.5 parts;
[0187] Xylene: 4 parts;
[0188] n-Butanol: 2 parts;
[0189] Z15 polyamide wax: 0.3 parts;
[0190] TQ200 fumed silica: 0.2 parts;
[0191] PZ20 zinc phosphate: 8 parts;
[0192] Barium sulfate: 11 parts;
[0193] 1051 Adhesion Promoter: 1 part;
[0194] Conductive material-zinc powder integrated material: 60 parts.
[0195] The total amount of the above raw materials is 100 parts. The epoxy resin used is E20 epoxy resin or E44 epoxy resin; the conductive material-zinc powder integrated material is the conductive material-zinc powder integrated material prepared in Example 1 or Example 2.
[0196] According to the above formula, epoxy resin, LA300 toughening resin, and JS-225 dispersant were added sequentially to the production tank, followed by xylene and n-butanol. The mixture was stirred at 700 rpm for 5 minutes. While stirring, Z15 polyamide wax, TQ200 fumed silica, PZ20 zinc phosphate, and barium sulfate were added slowly in sequence. After adding zirconium beads, the mixture was ground and dispersed for 1 hour until the fineness of the resulting coating base was less than 50 μm. Subsequently, 1051 adhesion promoter was added, and the mixture was stirred at 900 rpm for 20 minutes. After filtration, the epoxy coating base was obtained.
[0197] Taking the preparation of 300g of component A as an example, the epoxy coating base material prepared according to the above formula is 120g. The 120g epoxy coating base material is added to the production tank, and 180g of conductive material-zinc powder integrated material is slowly added under the stirring condition of 1000r / min; after the addition is completed, stirring is continued for 30min to make the conductive material-zinc powder integrated material uniformly dispersed, thus obtaining component A.
[0198] By using conductive materials with different types or contents of conductive functional materials integrated with zinc powder, component A can be prepared accordingly, including integrated epoxy zinc-rich coatings of carbon nanotubes and zinc powder, pre-dispersed integrated epoxy zinc-rich coatings of carbon nanotubes and zinc powder, integrated epoxy zinc-rich coatings of graphene and zinc powder, integrated epoxy zinc-rich coatings of graphite and zinc powder, integrated epoxy zinc-rich coatings of nickel and zinc powder, or integrated epoxy zinc-rich coatings of copper and silver powder and zinc powder.
[0199] (2) Preparation of component B
[0200] Component B is made from the following raw materials in parts by weight:
[0201] 498 epoxy curing agent: 70 parts;
[0202] Xylene: 19 parts;
[0203] n-Butanol: 9 parts;
[0204] 1121 Additive: 2 parts.
[0205] Add 498 epoxy curing agent, xylene, n-butanol and 1121 additive to the production tank and stir at 700 r / min for 10 min until the mixture is uniform to obtain component B.
[0206] (3) Preparation of coating
[0207] Before application, component A and component B are mixed evenly at a mass ratio of 10:1 to obtain a mixed coating. The application viscosity of the mixed coating is adjusted to 30–40 s as measured by a Ford cup using a mixed solvent composed of xylene and n-butanol.
[0208] The mixed coating with adjusted viscosity was sprayed onto the surfaces of tinplate and carbon steel substrates, respectively.
[0209] The dry film thickness of the coating sprayed onto the tinplate substrate surface was controlled to be 20–30 μm. The sprayed tinplate sample was placed in a constant temperature environment of 25°C for 48 hours to cure. The resulting sample was used to test the coating’s flexibility, impact resistance and cross-cut adhesion.
[0210] The dry film thickness of the coating sprayed onto the carbon steel substrate was controlled to be 80–100 μm. The carbon steel sample after spraying was cured for 7 days. The resulting sample was used to test the coating’s resistance to neutral salt spray, electrochemical properties and pull-out adhesion.
[0211] To investigate the integrated structure formed by pressure bonding and oxygen-free calcination of carbon nanotubes and zinc powder, scanning electron microscopy was used to observe zinc powder, carbon nanotubes, and carbon nanotube-zinc powder integrated materials, as well as to measure particle size and resistivity.
[0212] 1. Microscopic morphology analysis
[0213] Figure 1 Scanning electron microscope images of zinc powder, carbon nanotubes, and integrated carbon nanotube-zinc powder materials, among which... Figure 1 A in the text refers to zinc powder. Figure 1 B in the text represents carbon nanotubes. Figure 1 C in the text refers to an integrated carbon nanotube-zinc powder material obtained through oxygen-free calcination at 400℃. Figure 1 As can be seen from A in the figure, unmodified zinc powder mainly exhibits spherical or near-spherical particle morphology, with relatively uniform particle distribution, good dispersion between particles, and relatively uniform overall particle size. Figure 1As can be seen from B, carbon nanotubes intertwine and aggregate to form agglomerates, exhibiting the typical agglomeration morphology of nanomaterials due to their large specific surface area and strong intertube forces. Figure 1 As shown in Figure C, after pressure bonding and 400℃ anaerobic calcination, carbon nanotubes are tightly attached to, coated, or wrapped around the surface of zinc powder particles, extending outwards from the surface of the zinc powder particles. Some zinc powder particles exhibit morphological changes or localized collapse. This may be because the calcination temperature is close to the melting point of zinc, causing the zinc powder surface to soften or partially melt, thus fixing the carbon nanotubes to the zinc powder particle surface and forming a stable carbon nanotube-zinc powder composite interface. These results indicate that the combined pressure bonding and anaerobic calcination treatment can promote interfacial bonding between carbon nanotubes and zinc powder, enabling the carbon nanotubes to form an outwardly extending conductive structure on the zinc powder surface. This epitaxial structure facilitates bridging of adjacent zinc powder particles, thus providing a structural basis for forming a continuous and stable conductive network within the coating.
[0214] 2. Particle size analysis
[0215] After adding carbon nanotubes, the overall particle size of the resulting composite particles is larger than that of pure zinc powder, indicating that carbon nanotubes can connect adjacent zinc powder particles, enabling multiple zinc powder particles to form a composite structure.
[0216] For the CNTS / Zn integrated material prepared using carbon nanotube powder, the particle size of the composite material increased from 14.96 μm to 19.73 μm as the carbon nanotube content increased from 0.5% to 1.5%. These results indicate that the carbon nanotube content has a significant impact on the particle size of the integrated material. With increasing carbon nanotube content, the number of carbon nanotubes on the surface of the zinc powder particles and the degree of bridging between particles increase, thereby promoting the formation of larger composite particles. This particle size variation is consistent with the morphology of the carbon nanotube-connected zinc powder particles observed by scanning electron microscopy.
[0217] With the same carbon nanotube content, the particle size of the D-CNTS / Zn integrated material prepared using a carbon nanotube pre-dispersion solution is smaller than that of the CNTS / Zn integrated material prepared by direct mixing of carbon nanotube powder. This may be because pre-dispersion treatment improves the agglomeration state of carbon nanotubes, allowing them to be more uniformly distributed and fixed on the surface of zinc powder particles, reducing excessive aggregation of zinc powder particles caused by disordered agglomeration of carbon nanotubes. Therefore, using a pre-dispersion solution for mixing is beneficial for improving the uniformity of carbon nanotube loading on the zinc powder surface and for controlling the particle size of the integrated material.
[0218] 3. Resistivity Analysis
[0219] Figure 2The resistivity of carbon nanotube-zinc powder composites with different carbon nanotube contents and different preparation states is shown as a function of test pressure. Figure 2 The study compared pure zinc powder, uncalcined carbon nanotube-zinc powder physical mixtures, and calcined carbon nanotube-zinc powder integrated materials.
[0220] Depend on Figure 2 It can be seen that as the test pressure increased from 3 MPa to 10 MPa, the resistivity of all samples decreased with increasing pressure, showing a trend of initially decreasing rapidly and then gradually leveling off. This may be because, with increasing pressure, the porosity inside the powder decreases, the contact between zinc powder particles and carbon nanotubes becomes tighter, and the conductive contact points and conductive pathways between particles increase accordingly. When the pressure increases to a certain level, the particle contact state inside the powder gradually stabilizes, thus the rate of decrease in resistivity decreases accordingly.
[0221] Under the same test pressure, the resistivity of the composite material containing carbon nanotubes was generally lower than that of pure zinc powder; furthermore, the resistivity of the composite material decreased further with increasing carbon nanotube content. This result indicates that carbon nanotubes can form conductive bridging structures between zinc powder particles, expanding the effective conductive range of the zinc powder particles and reducing the electron transport resistance between adjacent zinc powder particles, thereby improving the conductivity of the composite material. With increasing carbon nanotube content, the probability of forming conductive pathways between zinc powder particles increases, resulting in a more complete conductive network.
[0222] Further comparison of the physical hybrid material and the calcined integrated material with the same carbon nanotube content shows that, under the same test pressure, the resistivity of the uncalcined carbon nanotube-zinc powder physical hybrid material is lower than that of the corresponding calcined integrated material, and the difference between the two is relatively obvious in the low pressure region; as the test pressure increases, the difference in resistivity between the two gradually decreases.
[0223] The resistivity of the integrated material increased slightly after calcination, possibly because the zinc powder surface softened or partially melted during the calcination process, and some carbon nanotubes were covered by zinc or a small amount of oxide products on the zinc surface, thus affecting local electron transport. Nevertheless, the resistivity of the calcined integrated material was still significantly lower than that of pure zinc powder, indicating that the calcination treatment did not destroy the main conductive structure formed by the carbon nanotubes, and the resulting integrated material still maintained good conductivity.
[0224] By premixing carbon nanotubes with zinc powder, pressure binding, and calcining under anaerobic conditions, carbon nanotubes can be fixed onto the surface of zinc powder particles to form an epitaxial conductive structure. This structure not only enhances the interfacial bonding between carbon nanotubes and zinc powder but also bridges adjacent zinc powder particles through the carbon nanotubes, providing a foundation for constructing a stable conductive network and improving the utilization efficiency of zinc powder in zinc-rich or zinc-containing anti-corrosion coatings.
[0225] Electrochemical performance and salt spray resistance analysis
[0226] Coating samples with a dry film thickness of approximately 120 μm were prepared using E44 epoxy resin with a high epoxy value. Each coating sample was tested according to the aforementioned electrochemical impedance spectroscopy method to investigate the effect of the carbon nanotube-zinc powder integrated material on the long-term shielding performance of the coating.
[0227] Figure 3 The shielding resistance curves of pure zinc-rich coatings and modified zinc powder coatings with different carbon nanotube contents as a function of immersion time are shown. Figure 3 It can be seen that the shielding resistance of each coating generally decreases with prolonged immersion time. This is because during the immersion process, NaCl electrolyte gradually penetrates into the coating through micropores or local defects, causing the physical shielding effect of the coating to gradually weaken.
[0228] Among them, the shielding resistance of the pure zinc-rich coating decreased most significantly, dropping rapidly in the initial stage of immersion and remaining at a low level in the later stage. After immersion for 5280 hours, the shielding resistance of the pure zinc-rich coating decreased to 1.7 × 10^6 Ω·cm². This trend is basically consistent with the trend of the coating's low-frequency impedance modulus changing with immersion time.
[0229] Compared with pure zinc-rich coatings, coatings prepared with carbon nanotube-modified zinc powder exhibited better long-term shielding performance. After immersion for 500 hours, the shielding resistance of all carbon nanotube-modified zinc powder coatings was higher than that of pure zinc-rich coatings. Furthermore, within the range of carbon nanotube addition used in this experiment, the shielding resistance of the coatings generally increased with increasing carbon nanotube content. Among them, the coating containing 1.5% CNTS / Zn integrated material showed the smallest decrease in shielding resistance throughout the entire immersion period. After immersion for 5280 hours, the shielding resistance of this coating still reached 4.6 × 10^8 Ω·cm², which is 1 to 2 orders of magnitude higher than that of other carbon nanotube-modified zinc powder coatings.
[0230] The above results demonstrate that carbon nanotubes can form a barrier network structure within the coating, reducing or delaying the penetration of electrolytes into the metal substrate through pores and defects within the coating. Carbon nanotubes possess a high aspect ratio and good structural integrity. Once fixed to the surface of zinc powder particles, they not only bridge adjacent zinc powder particles but also increase the tortuosity of the penetration path of corrosive media within the coating, thereby improving the long-term shielding performance of the coating. Within the scope of this experiment, increasing the carbon nanotube content is beneficial for improving the integrity of the aforementioned network structure, thus correspondingly enhancing the shielding effect of the coating.
[0231] Furthermore, the shielding resistance of the D-CNTS / Zn integrated material obtained by premixing carbon nanotubes with zinc powder and then calcining is significantly higher than that of the modified coating obtained using undispersed carbon nanotubes. Particularly in the later stages of immersion, the shielding resistance of the 1.5% D-CNTS / Zn integrated material coating obtained by premixing and calcining with the dispersion is approximately 4 to 18 times that of the undispersed coating. This may be because the predisposition treatment improves the uniformity of carbon nanotube distribution on the zinc powder surface, reduces local porosity or structural defects caused by carbon nanotube agglomeration, and allows the carbon nanotubes to be more uniformly fixed on the zinc powder particle surface, forming a more continuous and stable barrier and conductive network.
[0232] To further evaluate the impact of carbon nanotube introduction methods on the corrosion resistance of zinc-rich coatings, salt spray test specimens with a dry film thickness of approximately 80 μm were prepared using low-epoxy-value E20 epoxy resin to accelerate the corrosion failure process of the coatings. Pure zinc coatings with zinc powder contents of 60 wt% and 70 wt% were used as controls, and compared with a composite coating containing 60 wt% zinc powder and carbon nanotube-modified zinc powder. Carbon nanotubes were introduced into the coatings via physical mixing and calcination integration, respectively. The experimental results are as follows: Figure 4 As shown.
[0233] Depend on Figure 4 It was found that after a 360-hour neutral salt spray test, both pure zinc coatings with zinc powder contents of 60wt% and 70wt% exhibited significant red rust on the coating surface and at the scratched areas. The rust spread from the scratches to the surrounding areas, accompanied by severe blistering, indicating that the metal substrate beneath the coating had undergone significant corrosion. After the salt spray test, the adhesion of both pure zinc coatings decreased to approximately 1 MPa, indicating that the coating structure and the bond between the coating and the substrate had been severely damaged.
[0234] In contrast, the coating with carbon nanotube-modified zinc powder, after an extended salt spray test of 720 hours, did not exhibit the large-area corrosion and severe blistering seen in the pure zinc coating, regardless of the tested carbon nanotube addition amounts and methods. This indicates that, at a zinc powder content of 60 wt%, the coating formed by introducing carbon nanotube-modified zinc powder exhibits significantly better salt spray resistance than the pure zinc coating with the same zinc powder content, and even better than the pure zinc coating with a zinc powder content increased to 70 wt%. Carbon nanotubes can strengthen the electrical connections between zinc powder particles, allowing more zinc powder to participate in the electrochemical protection process, thereby improving the coating's sacrificial anodic protection capability against the metal substrate.
[0235] Further comparison of different methods of introducing carbon nanotubes reveals that the CNTS / Zn integrated material coating prepared using a calcination-integrated process exhibits superior corrosion resistance compared to coatings formed by directly mixing carbon nanotubes and zinc powder. For example... Figure 4 As shown in figures a to c, coatings prepared using a physical mixture of carbon nanotubes and zinc powder all exhibited varying degrees of localized corrosion after 720 hours of salt spray testing. While their adhesion remained higher than that of pure zinc coatings, it decreased by approximately 65% compared to before the salt spray test. The CNTS / Zn integrated material coating prepared using a calcination-integrated process showed only slight localized whitening on the coating surface or near scratches after 720 hours of salt spray testing, with no obvious red rust or corrosion expansion observed. This whitening phenomenon mainly originated from the white corrosion products formed after the anodic dissolution of zinc, indicating that the zinc powder in the coating effectively played a sacrificial anodic protection role. Furthermore, the adhesion reduction of the integrated material coatings with the three carbon nanotube addition amounts after the salt spray test was less than that of the corresponding physical mixture coatings.
[0236] The above results demonstrate that pressure bonding and anaerobic calcination treatment enable carbon nanotubes and zinc powder particles to form a more compact and stable integrated structure, enriching and fixing the carbon nanotubes on the surface of the zinc powder particles, forming a conductive domain extending outward from the zinc powder surface. This epitaxial conductive domain can improve the connectivity between adjacent zinc powder particles, reduce the electrochemical isolation of zinc powder caused by resin isolation, and facilitate the construction of a continuous conductive network within the coating. Therefore, compared with pure zinc powder systems and physical mixtures of carbon nanotubes and zinc powder, the coating prepared using CNTS / Zn integrated material exhibits stronger cathodic protection, better coating density, and higher adhesion retention.
[0237] Example 5: Preparation of graphite filler-zinc powder integrated material and its performance evaluation in epoxy zinc-rich coating.
[0238] To further verify the effect of the integrated structure of sheet-like carbon-based conductive material and zinc powder on the anti-corrosion performance of epoxy zinc-rich coating, graphene and graphite were selected as sheet-like graphite conductive fillers, respectively. Integrated graphene-zinc powder materials and integrated graphite-zinc powder materials were prepared according to the aforementioned dry-mixing and calcination method. The addition amounts of graphene and graphite were 1%, 2.5%, and 5%, respectively.
[0239] The microstructure of the integrated materials obtained with different flake graphite fillers and different addition amounts was observed using scanning electron microscopy. For the graphene-zinc powder integrated material, the zinc powder mainly exhibited a near-spherical morphology with a relatively smooth surface; graphene existed in a flake structure and was distributed on the surface and between the zinc powder particles. With increasing graphene addition, the distribution of flake graphene among the zinc powder particles changed. When the graphene addition was 1%, the flake graphene was relatively uniformly dispersed among the zinc powder particles, with only a small amount of local stacking; when the graphene addition increased to 2.5%, the agglomeration of the graphene flake structure was enhanced, with some areas forming thicker flake stacks; when the graphene addition reached 5%, the agglomeration degree of the graphene flakes further increased, forming a more obvious aggregated structure between the zinc powder particles. For the graphene-zinc powder integrated material, the zinc powder also mainly exhibited a near-spherical morphology with a relatively smooth surface; graphite was grafted and attached to the surface and between the zinc powder particles in the form of irregular particles or flake structures. As the graphite content increased from 1% to 2.5% and 5%, the distribution and agglomeration of graphite among zinc powder particles showed significant differences. When the graphite content was 1%, the graphite particles were well dispersed among the zinc powder particles, with only a small amount of local aggregation. When the graphite content was 2.5%, the agglomeration of graphite was enhanced, with small-scale particle stacking in some areas. When the graphite content was 5%, the degree of graphite agglomeration was further intensified, forming obvious aggregate structures among the zinc powder particles, which led to a significant reduction in the mixing uniformity and load dispersion of zinc powder and graphite in the composite material.
[0240] To evaluate the impact of graphene-based materials on the corrosion resistance of zinc-rich coatings, graphene was selected as a representative conductive additive, and salt spray resistance tests were conducted in both rapid and slow corrosion systems. The rapid corrosion system used E20 resin, with a coating thickness of approximately 80 μm; the slow corrosion system used E44 resin, with a coating thickness of approximately 120 μm. 1% and 5% of integrated graphene-zinc powder particles and corresponding physical mixtures were introduced into the experiments, with pure zinc coatings containing 60% and 70% zinc powder serving as controls to compare the effects of different resin systems, zinc powder types, and composite methods on the corrosion resistance of the coatings. The testing time for the pure zinc coating in the E20 system was 360 h, while the testing time for the graphene-modified coating was extended to 720 h; the salt spray testing time for the E44 system was 2000 h for all systems.
[0241] Salt spray test results showed that the pure zinc coatings in both resin systems exhibited poor salt spray resistance. In the E20 rapid corrosion system, after 360 hours of salt spray testing, numerous bubbles appeared on the surface of the pure zinc coating, the corrosion area expanded significantly, and the adhesion decreased significantly to approximately 1 MPa, a reduction of 80%. In the E44 system, although the pure zinc coating did not show obvious blistering, the corrosion at the scratches was severely extended, and the corrosion width of the coating with a zinc content of 60% was greater than that of the coating with a zinc content of 70%, indicating that the pure zinc coating with a zinc content of 60% had relatively weaker corrosion resistance.
[0242] Compared to pure zinc coatings, the introduction of graphene significantly improved the corrosion resistance of coatings in both resin systems. No large-area corrosion similar to that observed in pure zinc coatings was observed in any of the samples with added graphene, indicating that the addition of graphene effectively enhances the protective performance of epoxy zinc-rich coatings.
[0243] Further comparison of different graphene introduction methods revealed that, at a graphene addition of 1%, neither the physically mixed sample nor the calcined integrated sample showed significant corrosion. However, the calcined integrated sample exhibited a higher adhesion retention rate after salt spray testing. This result indicates that, at lower graphene addition levels, calcination integration treatment is beneficial for improving the interfacial stability of the coating after service life.
[0244] When the graphene addition was 5%, the difference in corrosion resistance between the two introduction methods became more pronounced. In the E20 system, the physically mixed sample exhibited large-scale corrosion that spread outwards, such as... Figure 5 As shown in b; while the calcined integrated sample only showed a small amount of pitting corrosion at the edges, such as Figure 5 As shown in d, in the E44 system, obvious red rust appeared at the scratches of the physically mixed sample; in contrast, the calcined integrated sample only produced white corrosion products, namely zinc white, at the scratches, with no obvious corrosion extension. This white corrosion product indicates that the zinc powder in the coating played a sacrificial anodic protection role, and the coating substrate was not significantly damaged. The zinc around the scratches provided strong cathodic protection to the substrate at the scratches, while the corrosion products formed after the anodic zinc dissolved sealed the scratched area, thus effectively isolating the base metal from contact with salt spray droplets.
[0245] Furthermore, with a graphene content of 5%, the adhesion of the calcined integrated sample decreased much less than that of the physically mixed sample, further demonstrating that the graphene-zinc powder integrated structure formed by the calcination process can improve the adhesion retention performance of the coating after long-term service.
[0246] The above results demonstrate that the introduction of graphene significantly improves the salt spray resistance of both E20 and E44 epoxy resin coatings. Furthermore, compared to a simple physical mixing of graphene and zinc powder, the graphene-zinc powder composite material prepared using an integrated calcination process exhibits superior corrosion resistance and adhesion retention. These results indicate that the integrated calcination process not only enhances the electrical connections between zinc powder particles and improves the cathodic protection efficiency of the zinc powder in the coating, but also improves coating density and maintains the bonding strength between the coating and the substrate. Therefore, it is more suitable for preparing high-protection, long-life epoxy zinc-rich coatings.
[0247] From the perspective of corrosion protection mechanism, the improvement of the corrosion protection performance of epoxy zinc-rich coating by sheet-like carbon-based materials, especially graphene and graphite, mainly comes from the synergistic enhancement of the physical shielding effect and cathodic protection effect produced by the integrated structure of "epitaxy conductive functional agent-zinc powder".
[0248] On the one hand, graphene possesses high conductivity and a two-dimensional sheet-like structure. Through integrated calcination processing, graphene can form epitaxial conductive domains on the surface of zinc powder, essentially constructing conductive extension arms on the surface of zinc powder particles. This expands the effective conductive radius of the zinc powder and precisely bridges adjacent zinc powder particles in the coating, forming a continuous conductive network. Compared to the traditional method of directly dispersing conductive additives in the coating system, this integrated structure can achieve more effective electrical connections of zinc powder with a lower amount of conductive additives and reduces conductive dead zones caused by conductive additive agglomeration or insufficient compatibility with the resin. Consequently, the electron transfer resistance between zinc powder particles within the coating is reduced, the cathodic protection effect is more uniform, and the localized excessive consumption of zinc powder is delayed.
[0249] Although graphite has lower electrical conductivity than graphene, its layered structure can still bridge zinc powder particles and promote electron transfer to some extent. As the graphite content increases, the integrity of the conductive network improves; however, due to the inherent conductivity of graphite and limitations in interlayer spacing, at the same addition amount, graphite's effect on improving the cathodic protection performance of the coating is weaker than that of graphene. The calcination process can strengthen the interfacial bonding between the sheet-like carbon-based material and zinc powder, improve the stability of the conductive network, and thus enhance the long-term effectiveness of cathodic protection.
[0250] On the other hand, graphene, with its dense single-atom-layer structure and high aspect ratio, can form a labyrinthine barrier network in coatings, effectively blocking the penetration of corrosive media and extending their diffusion paths. Simultaneously, graphene exhibits high chemical stability, which helps maintain the long-term integrity of this barrier network. Graphite also possesses a layered structure, offering some barrier effect against corrosive media; however, due to its relatively insufficient interlayer spacing and dispersion uniformity, its barrier effect is weaker than that of graphene. With increasing graphite content, the stacking density of graphite sheets increases, improving the coating's barrier performance somewhat; however, even at an addition level of 5%, its barrier effect still falls short of graphene's level due to structural defects.
[0251] In summary, the integrated carbon-based sheet material and zinc powder can simultaneously function as a conductive network constructor and a physical shield in epoxy zinc-rich coatings. The physical shielding effect delays the penetration of corrosive media into the coating interior, reduces zinc powder consumption, and thus extends the cathodic protection time. Conversely, the cathodic protection effect inhibits localized corrosion at coating defects, maintaining the integrity of the physical shielding network. This synergistic effect results in epoxy zinc-rich coatings modified with the integrated carbon-based sheet material and zinc powder exhibiting superior corrosion resistance compared to traditional pure zinc-rich coatings and physically modified coatings.
[0252] Example 5: Preparation of an integrated conductive material-zinc powder material (microwave calcination method)
[0253] Take 100 g of 600-mesh zinc powder and 1.0 g of carbon nanotube powder. Add the carbon nanotube powder to 20 g of xylene and first ultrasonically disperse for 10 min to allow the carbon nanotubes to be initially wetted and dispersed in the xylene. Then, while stirring in a disperser at 300 rpm, slowly add the zinc powder and continue stirring for 10 min. Then, add zirconium beads and disperse at a low speed of 600 rpm for 30 min to ensure that the carbon nanotubes and zinc powder are in full contact, thus obtaining a carbon nanotube / zinc powder mixed slurry.
[0254] The above-mentioned mixed slurry was subjected to solid-liquid separation using a vacuum filter. The resulting filter cake was placed in a vacuum oven and dried under vacuum at 60°C for 6 hours to obtain a carbon nanotube / zinc powder physical mixture. The obtained physical mixture powder was placed in a tableting mold and pressed under a pressure of 10 MPa for 2 minutes to form a powder cake with a diameter of approximately 30 mm and a thickness of approximately 5 mm.
[0255] The powder cake was placed in a covered alumina crucible, and the alumina crucible was placed in the constant temperature zone of a microwave tube furnace. To improve the uniformity of heating, a silicon carbide auxiliary microwave absorber was placed around the outer periphery of the crucible. After the furnace was closed, high-purity nitrogen was first introduced for 30 minutes to purge the air from the furnace cavity, with a nitrogen flow rate of 0.5 L / min. Subsequently, the nitrogen flow rate was adjusted to 0.2 L / min and a slight positive pressure protection was maintained throughout the microwave calcination process.
[0256] Start the microwave heating device at a frequency of 2450 MHz, using temperature control mode. The initial microwave output power is 800 W, which is automatically adjusted according to the oven temperature. Heat to 390°C at a rate of approximately 8°C / min, and hold at 390°C for 30 minutes. After holding, turn off the microwave heating and allow the mixture to cool naturally to below 80°C under nitrogen protection. Remove the calcined powder cake.
[0257] The cooled calcined product is lightly crushed and ground, and then sieved through a 200-mesh sieve and a 400-mesh sieve in sequence. The fine powder that passes through the 200-mesh sieve and cannot be completely agglomerated is collected to obtain the carbon nanotube-zinc powder integrated material, denoted as 1%CNTS / Zn-MW.
[0258] During this microwave calcination process, carbon nanotubes, acting as a microwave absorbing phase, preferentially absorb microwave energy and generate a localized thermal effect in the contact area with zinc powder particles. This softens or slightly melts the surface of the zinc powder particles, thereby fixing, embedding, or wrapping the carbon nanotubes onto the surface of the zinc powder particles, forming a conductive material-zinc powder integrated material with an epitaxial conductive structure. This material can be used as a functional filler in zinc-rich or zinc-containing anti-corrosion coatings.
[0259] Example 6 Preparation of an integrated conductive material-zinc powder material (conductive polymer bonding method)
[0260] In this embodiment, carbon nanotubes are used as conductive functional materials and conductive polyaniline is used as a conductive polymer to prepare an integrated carbon nanotube-polyaniline-zinc powder material.
[0261] Take 2.0 g of dodecylbenzenesulfonic acid-doped conductive polyaniline powder and add it to 40 g of a mixed solvent composed of xylene, n-butanol and N-methylpyrrolidone in a mass ratio of 6:3:1. Disperse the mixture by ultrasonication for 20 min and then by high-speed dispersion at 1200 rpm for 30 min to obtain a polyaniline conductive adhesive dispersion.
[0262] Subsequently, 1.0 g of carbon nanotube powder was added to the above polyaniline conductive binder dispersion, and ultrasonic dispersion was continued for 15 min. Then, the mixture was stirred at 1000 rpm for 20 min to ensure that the carbon nanotubes were fully wetted and dispersed by the polyaniline, thus obtaining a carbon nanotube / polyaniline composite conductive dispersion.
[0263] Take another 100 g of 600-mesh zinc powder and place it in a dispersion container equipped with a stirrer. Add 20 g of xylene and stir at 300 rpm for 5 min under nitrogen protection. Then, while continuously stirring, slowly add the above carbon nanotube / polyaniline composite conductive dispersion to the zinc powder. After the addition is complete, add zirconium beads and disperse at a low speed of 600 rpm for 45 min to ensure sufficient contact between the carbon nanotubes, polyaniline, and zinc powder, thus obtaining a carbon nanotube / polyaniline / zinc powder mixed slurry.
[0264] The above-mentioned mixed slurry was subjected to solid-liquid separation using a vacuum filter. The resulting filter cake was placed in a vacuum oven and dried under vacuum at 60°C for 8 hours to remove most of the solvent. The dried powder was then placed in a nitrogen atmosphere and heat-treated at 120°C for 1 hour to allow the polyaniline conductive polymer to further form a film and shrink and solidify, thereby adhering and fixing the carbon nanotubes to the surface of the zinc powder particles.
[0265] After heat treatment, the powder is naturally cooled to room temperature under nitrogen protection. The powder is then removed, lightly ground and crushed, and then sieved through a 200-mesh sieve and a 400-mesh sieve in sequence. The sieved powder is collected to obtain the integrated carbon nanotube-polyaniline-zinc powder material, denoted as CNTS-PANI / Zn.
[0266] In this integrated material, polyaniline, as a conductive polymer binder, at least partially coats or adheres to the surface of zinc powder particles, and also binds carbon nanotubes to the surface of the zinc powder particles. The carbon nanotubes form an epitaxial conductive structure on the zinc powder surface, and since polyaniline itself is also conductive, it does not significantly block electron transfer between the zinc powder and the carbon nanotubes. The resulting CNTS-PANI / Zn integrated material can be used as a conductive functional filler in zinc-rich or zinc-containing anti-corrosion coatings.
[0267] To further investigate the relationship between pressure and CNT loading on the resistivity of the resulting conductive composite material during the manufacturing process, this patent constructs a model for predicting the resistivity of the composite material under different conditions. The derivation process is as follows:
[0268] According to Holm's contact theory, the contact resistance between two conductive particles With contact spot radius Inversely proportional to the actual contact area, for soft metals like zinc powder, under pressure ranges of 3-10 MPa, particle contact mainly involves plastic deformation. With applied pressure Proportional, therefore, the change in resistance at a single contact point caused by pressure is: Considering that the powder is a multi-particle stacking system, the number of conductive channels... It also increases with pressure, so the actual index is usually greater than 0.5. Set it as a parameter to be determined. .
[0269] For composite materials, electrical conductivity Volume fraction of conductive filler It usually follows a power-law relationship:
[0270]
[0271] because (0.5% - 1.5%) is far higher than the typical percolation threshold of nanotubes, and the patented technology uses surface anchoring to optimize network connectivity, making the threshold negligible. Simplified to:
[0272]
[0273] These are the parameters to be fitted.
[0274] Due to resistivity It is the reciprocal of conductivity, and in this integrated conductive material, the total resistance is composed of countless parallel and series microscopic contact units, while the pressure during the manufacturing process... The number and area of contact points are increased, and the load capacity is improved through CNT bridging. Since the transmission efficiency at each contact point is increased, assuming that the two effects are physically independent, i.e., the presence of CNT does not significantly change the plastic yield stress of zinc powder, the contributions of the two can be constructed as a power-law model in product form. ;
[0275] Convert to: ;
[0276] In the formula, It is the resistivity of the composite material. It refers to the loading amount of carbon nanotubes. It is the applied pressure value.
[0277] Based on the results of the coating test, randomly select Figure 9 Half of the data at different time points under conditions of 0.5% CNTS / Zn, 1% CNTS / Zn, and 1.5% CNTS / Zn were used as the fitting data, and the other half were used as the validation data. The model was then fitted, and the results on the fitting and validation data yielded K=131.42. = 3.14, =2.20, fitted sample R 2 =0.9981, validation sample R 2=0.9573, the comparison between the experimental data and predicted values of the fitted sample and the validation sample are as follows: Figure 6 and Figure 7 As shown, the resistivity of all samples changes with pressure and CNT loading as follows: Figure 8 As shown in the figure, this method has good predictive performance.
[0278] To further investigate the effects of CNT load and immersion time on the low-frequency impedance modulus, this patent also constructs a prediction method model for predicting the low-frequency impedance modulus under different conditions. The derivation process is as follows:
[0279] First, we make the following assumption: at a low frequency of 0.01Hz, the impedance modulus mainly reflects the combined effect of restricted ion conduction in the coating's pore channels and interfacial polarization. Therefore, we will... Considered a characteristic quantity characterizing the effective shielding impedance of the coating, its change with immersion time is dominated by the penetration process of the electrolyte in the coating; simultaneously, the transport of electrolyte in the coating is dominated by diffusion, and can be represented by the effective diffusion coefficient. Characterization; Simultaneously considering that CNT-loaded zinc nanoparticles form a network structure in the coating and alter the diffusion path tortuosity and pore connectivity, Follow The CNT-loaded zinc nanoparticles are modified; furthermore, impedance attenuation is equivalent to a first-order process controlled by a single characteristic time constant; the local rebound and plateau effect caused by corrosion product blockage are equivalently absorbed in this model as the characteristic time constant changes with... It increases as it increases.
[0280] Let the coating thickness be Electrolyte concentration is Its diffusion in the coating thickness direction can be characterized by the following formula:
[0281]
[0282] For a diffusion system of thickness L, the diffusion process exhibits a characteristic timescale that is proportional to the square of the thickness and inversely proportional to the effective diffusion coefficient. Let it be:
[0283]
[0284] CNT-loaded zinc nanoparticles form a high aspect ratio conductive connection and filling structure in the coating, which can simultaneously increase the tortuosity of the diffusion channels and reduce the effective interconnected pores. Therefore, a randomized controlled diffusion method can be used. Increased tortuosity enhancement factor To describe its inhibitory effect on diffusion, let's assume:
[0285]
[0286] in The characteristic loading level reflects the content scale at which the CNT network effect begins to take effect significantly. The tortuosity enhancement factor is applied to the diffusion coefficient, setting the baseline effective diffusion coefficient to be... ,but:
[0287]
[0288] Substituting the feature time scale, we get:
[0289]
[0290] Let the quasi-diffusion characteristic time constant be... Then we can obtain:
[0291]
[0292] During the immersion process, as the electrolyte penetrates, the shielding ability of the coating decreases, and the low-frequency impedance characteristics... It decays over time. This decay process is equivalent to... The first-order process of control:
[0293]
[0294] For the above expression, given Integrating, we obtain the exponential solution. Let the initial impedance be... :
[0295]
[0296] Substituting the values, we obtain the final model form:
[0297]
[0298] In the formula is , , These are the parameters to be fitted.
[0299] Based on the results of the coating test, randomly select Figure 9 Half of the data at different time points under conditions of 0.5% CNTS / Zn, 1% CNTS / Zn, and 1.5% CNTS / Zn were used as the fitting data, and the other half were used as the validation data. The model was then fitted, and the results on the fitting and validation data were obtained as follows: =1.174408e+10 Ohm·cm 2 , =532.501414 h, =0.774089 wt%. Fitted sample R0 2 = 0.8009, validation sample R 2 = 0.7610. The comparisons between the experimental data and predicted values for the fitted and validation samples are as follows: Figure 9 and Figure 10 As shown, the low-frequency impedance magnitude of all samples changes with time and CNT load as follows: Figure 11 As shown in the figure, this method has good predictive performance.
Claims
1. A conductive material-zinc powder integrated material for zinc-rich / zinc-containing anti-corrosion coatings, wherein the conductive material-zinc powder integrated material is composed of zinc powder particles and a conductive functional material compounded by calcination.
2. The conductive material-zinc powder integrated material according to claim 1, characterized in that, The conductive functional material is selected from at least one of the following conductive materials: carbon nanotubes, graphene, graphite, conductive nickel, or copper-silver powder; the content of the conductive functional material is 0.1-30 wt% based on the total mass of the integrated conductive material and zinc powder. The content of the conductive functional material is 0.3-20 wt%; the content of the conductive functional material is 0.5-10 wt%.
3. The conductive material-zinc powder integrated material according to claim 1, characterized in that, When the conductive functional material is carbon nanotube, its content is 0.3-5 wt%; or when the conductive functional material is graphene and / or graphite, its content is 0.5-10 wt%; or when the conductive functional material is conductive nickel, its content is 5-30 wt%. The preparation methods for conductive material-zinc powder integrated materials include dry mixing and calcination, liquid pre-dispersion and calcination, microwave calcination, or bonding zinc powder particles and conductive functional materials with conductive polymers.
4. The conductive material-zinc powder integrated material according to claim 1, characterized in that, The dry-mixing calcination method includes the following steps: (a) mixing and dispersing the powder, which is the conductive functional material, with zinc powder in an organic solvent to obtain a mixture; (b) performing solid-liquid separation and drying on the mixture from step (a) to obtain a physically mixed powder; (c) pressure binding the physically mixed powder from step (b) and pressing it into shape; (d) calcining the shape from step (c) under a vacuum or inert atmosphere; and (e) pulverizing and sieving the calcined product from step (d).
5. The conductive material-zinc powder integrated material according to claim 4, characterized in that, In the dry-mix calcination method, the pressing pressure in step (c) is 1-30 MPa; the calcination temperature in step (d) is 250-650℃, and the calcination time is 0.2-4h.
6. The conductive material-zinc powder integrated material according to claim 1, characterized in that, The liquid pre-dispersion calcination method includes the following steps: (a) mixing and dispersing a pre-dispersion liquid containing the conductive functional material with zinc powder to obtain a mixture; (b) performing solid-liquid separation and drying on the mixture from step (a) to obtain a physically mixed powder; (c) pressure binding the physically mixed powder from step (b) and pressing it into shape; (d) calcining the shape from step (c) under an oxygen-free or inert atmosphere; and (e) pulverizing and sieving the calcined product from step (d).
7. The conductive material-zinc powder integrated material according to claim 6, characterized in that, In the liquid pre-dispersion calcination method, the solid content of the conductive functional material in the pre-dispersion liquid in step (a) is 1-10 wt%; the pressing pressure in step (c) is 2-30 MPa; and the calcination temperature in step (d) is 250-650℃ and the calcination time is 0.2-4 h.
8. A zinc-rich / zinc-containing coating, characterized in that, The zinc-rich / zinc-containing coating is one of solvent-based coatings, water-based coatings, and powder coatings, and contains the conductive material-zinc powder integrated material as described in claim 1, wherein the mass fraction of the conductive material-zinc powder integrated material in the coating is 30-85 wt%.
9. The zinc-rich / zinc-containing coating according to claim 8, characterized in that, The coating composition comprises component A and component B; component B is a curing agent component; component A comprises the following components by mass percentage: epoxy resin: 8-18 wt% Toughening resin: 0.5-2.5 wt%; Solvent: 3-12 wt%; Additives: 0.3-5.0 wt%; Rust-inhibiting pigments and / or extender fillers: 10-30 wt%; Conductive materials-zinc powder integrated materials: 30-85 wt%; The epoxy resin is selected from at least one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenolic epoxy resin, alicyclic epoxy resin or brominated epoxy resin; The solvent is selected from at least one of xylene, toluene, ethylbenzene, n-butanol, isopropanol, ethylene glycol ether solvents, ketone solvents, or ester solvents; The additives are selected from at least one of dispersants, thixotropic additives, defoamers, leveling agents, wax additives, fumed silica, adhesion promoters, or epoxy accelerators. The rust-preventive pigment is selected from at least one of zinc phosphate, composite zinc phosphate, or environmentally friendly zinc phosphate. The filler material is selected from at least one of barium sulfate, bentonite, or fumed silica.
10. The zinc-rich / zinc-containing coating according to claim 9, characterized in that, During the preparation of the integrated conductive material-zinc powder material, the resistivity of the resulting integrated conductive material-zinc powder material is kept within a set range by controlling the amount of conductive functional material added and the pressing pressure; the resistivity is calculated using the following formula: ; In the formula, It is the resistivity of the composite material. It is the load of the conductive material. It is the applied pressure value. , , These are the parameters to be fitted; The shielding resistance of the coating is measured by controlling the amount of conductive functional material added and the soaking time. The shielding resistance is calculated using the following formula for the impedance modulus at a low frequency of 0.01 Hz. get: The soaking time is And the carbon nanotube loading is When the coating is in impedance magnitude at Hz Soaking time, It is the carbon nanotube loading capacity, It is the initial low-frequency impedance scale, It is the reference diffusion characteristic time constant, It is the characteristic loading of the carbon nanotube network effect.
